2020
DOI: 10.1590/0102-311x00048619
|View full text |Cite
|
Sign up to set email alerts
|

Is the local food environment associated with excess body weight in adolescents in São Paulo, Brazil?

Abstract: The obesogenic environment stimulates an inadequate diet by hampering healthy choices. This cross-sectional study evaluated the association between the local food environment and the prevalence of overweight and obesity in a representative sample population of adolescents living in the city of São Paulo, Brazil, using multilevel logistic regression models. Among the adolescents, 29.6% were overweight/obese. There were no significant differences between food environment and adolescents’ weight status. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
0
9
0
3
Order By: Relevance
“…47 Two further fair quality studies reported associations between availability and dietary outcomes although without presenting whether this was statistically significant. 48 49 Further, 10 good studies found a significant association between an availability characteristic and a health outcome [50][51][52][53][54][55][56][57][58][59] as did 2 fair studies 60 61 and 1 further poor study. 62 Additionally, one poor study reported that prevalence of overweight and mean body mass index (BMI) trended in the same direction as the number of 'westernstyle' restaurants and convenience stores, however, no statistics were presented.…”
Section: Bmj Global Healthmentioning
confidence: 96%
“…47 Two further fair quality studies reported associations between availability and dietary outcomes although without presenting whether this was statistically significant. 48 49 Further, 10 good studies found a significant association between an availability characteristic and a health outcome [50][51][52][53][54][55][56][57][58][59] as did 2 fair studies 60 61 and 1 further poor study. 62 Additionally, one poor study reported that prevalence of overweight and mean body mass index (BMI) trended in the same direction as the number of 'westernstyle' restaurants and convenience stores, however, no statistics were presented.…”
Section: Bmj Global Healthmentioning
confidence: 96%
“…This might be due to the increasing trends of childhood and adolescent obesity that have plateaued or even slightly decreased in HICs in the last decade 96,97 . Although the included studies from LMICs were only conducted in Brazil, 28,31 China, 27,29,71 and Malaysia, 42 the three countries are highly representative of their respective regions, and they are all undergoing major socio‐economic transformations. To the best of our knowledge, this analysis was the first to extend research to country‐based economic levels, and despite limited resources in LMICs, their findings are comparable and consistent with previous studies at the regional 98 or individual economic level 85 .…”
Section: Discussionmentioning
confidence: 99%
“…28,29 For instance, Oreskovic et al found an inverse association between FFR accessibility and adolescent weight in highincome towns in Massachusetts, 30 which was consistent with results from a study in Guangdong, China 27 ; Tang et al reported that this association was either insignificant or positive in low-income towns in New Jersey, 26 and two studies in Brazil reached a similar conclusion. 28,31 Additionally, in the study by Williams et al, the availability of FFRs was positively associated with weight problems in boys but showed negative associations in girls 32 ; however, Chen et al reported quite different results. 33 Similar controversial findings exist across age groups.…”
mentioning
confidence: 97%
“…Although studies have provided evidence that a community’s food environment may be associated with nutritional status [ 15 , 16 , 17 ] and food consumption [ 18 , 19 ], there is little research on the association between the food environment and consumption of processed foods [ 20 ]. This investigation is of great importance because it explores the connection between consumption patterns based on food processing and their impact on health and disease conditions [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%